Implementation of Profit Sharing System for Shrimp Farmers in Improving Welfare (Case Study in Anggana District, Muara Pantuan Village, Genting, Kutai Kartanegara) - Yusran, Yusran (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The pond management system in Anggana District, Muara Pantuan Village, generally uses a profit-sharing system (mudharabah), where pond workers do not have their own land and work for the pond owner. All management costs are borne by the owner, with a trust-based cooperation without a time limit. This study aims to understand the implementation of the profit-sharing system between workers and pond owners and assess its impact on the welfare of both parties. This study uses a qualitative descriptive method with data collection through observation, interviews, and documentation. The sample consisted of 9 respondents, namely 3 pond owners and 6 pond workers. The results of the study showed that the mudharabah system was implemented verbally, where pond owners handed over their ponds to workers to manage, while all costs remained the responsibility of the owner. This system is in accordance with the principles of muamalah in Islam and has been proven to provide significant benefits, including improving the welfare of workers and pond owners in meeting their living needs, education, and housing.